2006
DOI: 10.1016/j.ygcen.2006.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Winter profile of plasma sex steroid levels in free-living male western diamond-backed rattlesnakes, Crotalus atrox (Serpentes: Viperidae)

Abstract: Recent Weld studies on the reproductive ecology of western diamond-backed rattlesnakes (Crotalus atrox) from populations in southern Ari typically inaccessible, but in southern Arizona, where environmental conditions are typically mild during winter, adult males frequently bask at or near the entrances of communal dens. Basking activity, therefore, oVers a unique logistical opportunity to assess the complete annual proWle of plasma sex steroid levels in males of a temperate reptile in nature. From November to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 38 publications
1
20
1
Order By: Relevance
“…The magnitude of elevated baseline CORT in the treatment snakes at sample 2 falls within previously reported baseline levels of free-ranging rattlesnakes, including the sister species C. oreganus (Holding et al 2014;Schuett et al 2004;Lutterschmidt et al 2009, Lind et al 2010. Compared to acute elevation during the stress series, CORT was elevated to a much smaller degree via implants.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…The magnitude of elevated baseline CORT in the treatment snakes at sample 2 falls within previously reported baseline levels of free-ranging rattlesnakes, including the sister species C. oreganus (Holding et al 2014;Schuett et al 2004;Lutterschmidt et al 2009, Lind et al 2010. Compared to acute elevation during the stress series, CORT was elevated to a much smaller degree via implants.…”
Section: Discussionsupporting
confidence: 80%
“…Sometimes, as in this study, no relationship between time-to-bleed and CORT is observed (Holding et al, 2014b;Hopkins & DuRant 2011), which is likely because samples were collected within an adequate timeframe before circulating CORT increased due to stress response to handling (Schuett et al 2004). …”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Many studies have investigated sex steroid hormone concentrations of species with known mating systems in an effort to correlate steroid hormone concentrations with events of the reproductive cycle [4,9,16,17,18,19,26,29]. Estradiol is produced by ovarian granulosa cells and it seems that it is the first stimulant for mating behavior (estrus period) and yolk protein synthesis along ovulation in female reptiles [8].…”
Section: Estradiol and Progesteronementioning
confidence: 99%
“…Due to their large body size and diverse mating systems, Crotaline snakes make an ideal model organism for studying the ecology and physiology of vertebrate reproduction (Beaupre and Duvall, 1998;Almeida-Santos et al, 2004;Schuett et al, 2006). Male…”
Section: Introductionmentioning
confidence: 99%